Spontaneous pregnancy in a patient with premature ovarian insufficiency – case report - Calik-Ksepka, Anna; Grymowicz, Monika; Bronkiewicz, Weronika; Urban, Aleksandra; Mierzejewski, Kamil; Rudnicka, Ewa; Smolarczyk, Roman (Menopause Review/Przegląd Menopauzalny, 2018)
Diagnosis of premature ovarian insufficiency is usually sudden and distressful for the patient in terms of facing infertility. However, some patients with POI have intermittent ovarian activity with an overall 5% probability of pregnancy. We report the case of 27-year-old woman with premature ovarian insufficiency treated with hormone replacement therapy, who six months after diagnosis conceived spontaneously. Apart from bleeding episodes in the first trimester, the pregnancy course was uneventful, and a healthy neonate was delivered. Women with premature ovarian insufficiency should be informed about the small but nonetheless real possibility of pregnancy.